The design of Aceh Coffee Museum in Banda Aceh - Muazzah Shavira Yusuf (Universitas Syiah Kuala, 2019)
Aceh is one of the largest coffee producer province in Indonesia. Coffee has a very important role in economic development. Drinking coffee has become a cultural culture in Aceh. The development of coffee in Aceh records its own history, so it is very representative there is a coffee museum was presented in Banda Aceh. Aceh Coffee Museum aims to provide information about coffee and attract the community to preserve and remember the culture of coffee in Aceh. Aceh Coffee Museum applies Architectural Analogy as a theme. The design was applying the coffee beans form where it emphasizes the form, aesthetics, and application of object equations which expected to show a new face for the city of Banda Aceh and architecturally will be able to convey a message as a form of communication between the form of the building and can display the function of the shape in it.